2021
DOI: 10.1089/ees.2020.0197
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Study of Ammonia Storage Characteristics of Selective Catalytic Reduction for Diesel Engines

Abstract: Non-road machinery is very important, but non-road machinery has problems such as working under complex operating conditions. Agricultural machinery is an important type of non-road machinery, which mainly relies on diesel engines due to their high fuel efficiencies. The exhaust temperature of agricultural machinery changes drastically under different working conditions. This article aims to research on pollution control of non-road machinery. Among the exhaust after treatment technologies, selective catalytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Nie et al 7 studied the influence of intake and exhaust throttling on SCR performance at different altitudes through bench tests, and the results showed that intake and exhaust throttling could effectively improve exhaust temperature, thus improving NO x conversion efficiency. Tan et al 8 investigated the effects of temperature on ammonia storage in SCR using genetic algorithms and found that the ammonia storage capacity in SCR increased first and then decreased with the increase in temperature and that in ammonia storage there was an uneven distribution in a ε pattern, which was more pronounced at low temperatures. Raza et al 9 studied the effects of exhaust temperature and ammonia-to-nitrogen ratio on the formation of N 2 O in SCR through bench tests, and the results showed that a higher ammonia-to-nitrogen ratio would lead to an increase in N 2 O, and the concentration of N 2 O was also higher at 200–250 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Nie et al 7 studied the influence of intake and exhaust throttling on SCR performance at different altitudes through bench tests, and the results showed that intake and exhaust throttling could effectively improve exhaust temperature, thus improving NO x conversion efficiency. Tan et al 8 investigated the effects of temperature on ammonia storage in SCR using genetic algorithms and found that the ammonia storage capacity in SCR increased first and then decreased with the increase in temperature and that in ammonia storage there was an uneven distribution in a ε pattern, which was more pronounced at low temperatures. Raza et al 9 studied the effects of exhaust temperature and ammonia-to-nitrogen ratio on the formation of N 2 O in SCR through bench tests, and the results showed that a higher ammonia-to-nitrogen ratio would lead to an increase in N 2 O, and the concentration of N 2 O was also higher at 200–250 °C.…”
Section: Introductionmentioning
confidence: 99%